Inducible nitric oxide synthase-expressing myeloid-derived suppressor cells regulated by interleukin 35 contribute to the pathogenesis of psoriasis - Zhang, Junfeng; Zhang, Yunsheng; Yang, Zhiya; Cheng, Dalei; Zhang, Hui; Wei, Li; Liu, Chen; Yan, Fenglian; Li, Chunxia; Dong, Guanjun; Wang, Changying; Shi, Dongmei; et al. (Frontiers in Immunology, 2023)
Although psoriasis is classified as a T cell-mediated inflammatory disease, the contribution of myeloid cells to the pathogenesis of psoriasis is not fully understood. In the present study, we demonstrated that the expression of the anti-inflammatory cytokine interleukin-35 (IL-35) was significantly increased in patients with psoriasis with a marked increase in the number of myeloid-derived suppressor cells (MDSCs). Similar results were obtained in an imiquimod-induced psoriasis mouse model. IL-35 reduced the total number of MDSCs and their subtypes in the spleens and psoriatic skin lesions, ameliorating psoriasis. IL-35 also reduced the expression of inducible nitric oxide synthase in MDSCs, although it had no significant effect on interleukin-10 expression. Adoptive transfer of MDSCs from imiquimod-challenged mice aggravated the disease and weakened the effect of IL-35 in the recipient mice. In addition, mice transferred with MDSCs isolated from inducible nitric oxide synthase knockout mice had milder disease than those with wild-type MDSCs. Furthermore, wild-type MDSCs reversed the effects of IL-35, while MDSCs isolated from inducible nitric oxide synthase knockout mice did not affect IL-35 treatment. In summary, IL-35 may play a critical role in the regulation of iNOS-expressing MDSCs in the pathogenesis of psoriasis, highlighting IL-35 as a novel therapeutic strategy for patients with chronic psoriasis or other cutaneous inflammatory diseases.